2008
DOI: 10.1002/jsfa.3447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary humate supplementation on performance, egg quality and egg yolk fatty acid composition in layers

Abstract: BACKGROUND: The objective of this study was to determine the effects of humate on performance, egg quality and egg yolk fatty acid (FA) composition in laying hens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This is in agreement with the findings of Hanafy et al (2008), who reported no significant differences in egg shape index, albumen percentage and yolk index with humic acid supplementation across the treatments. The conjugate base of humic acid as used by Macit et al (2009), reported that yolk colour improved with the supplementation of different levels in layer diets, which is similar with the findings of this study but in contrast with the reports of Dobrzañsk et al (2009), that yolk colour did not improve with supplementation of humic acid. In the present study, improved Haugh unit was observed in 0.4% humic acid diet, which is contrary to the findings of Abo-Egla et al (2011) who reported no significant effect of humic acid on 2.0, 4.0 or 6.0 mg of humic acid per kg was added in drinking water.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with the findings of Hanafy et al (2008), who reported no significant differences in egg shape index, albumen percentage and yolk index with humic acid supplementation across the treatments. The conjugate base of humic acid as used by Macit et al (2009), reported that yolk colour improved with the supplementation of different levels in layer diets, which is similar with the findings of this study but in contrast with the reports of Dobrzañsk et al (2009), that yolk colour did not improve with supplementation of humic acid. In the present study, improved Haugh unit was observed in 0.4% humic acid diet, which is contrary to the findings of Abo-Egla et al (2011) who reported no significant effect of humic acid on 2.0, 4.0 or 6.0 mg of humic acid per kg was added in drinking water.…”
Section: Discussionsupporting
confidence: 91%
“…Those authors also detected a significant increase in the USFA : SFA ratio in meat after 10% HS dietary supplementation. Macit et al (2009) reported an increase in SFA myristic acid and MUFA myristoleic, palmitoleic and heptadecenoic acids in egg yolks of layers fed a HS-supplemented diet. PUFA n-3 and PUFA n-6 levels in egg yolks remained unchanged by HS dietary treatments.…”
mentioning
confidence: 95%
“…The most important criterion for a consumer's choice of eggs is the yolk color. Egg yolk color is mainly determined by carotenoids and other pigmented substances —laying hens do not biosynthesize them— in the feed ( Macit et al, 2009 ). Lutein in carotenoids is absorbed by laying hens and deposited in eggs.…”
Section: Discussionmentioning
confidence: 99%